Association of FCGR2A rs1801274 and FCGR3A rs396991 polymorphisms with various autoimmune diseases: a meta-analysis - Thaler, Elena; Bublitz, Maike; Wipplinger, Martin; Gassner, Christoph; Ulmer, Hanno (Frontiers in Immunology, 2025)
ObjectivesThe aim of this systematic review with meta-analysis was to examine the association between the polymorphisms rs1801274 (FCGR2A H131R) and rs396991 (FCGR3A F158V) and susceptibility to autoimmune diseases (ADs), with a focus on the progress and novelty of studies published over the last two decades.MethodsA meta-analysis systematically evaluated FCGR2A/3A gene variants in autoimmune diseases (ADs) using four genetic models: dominant, recessive, overdominant, and allelic contrast.ResultsThe FCGR3A F158V polymorphism was significantly associated with immune thrombocytopenia in all four genetic models tested (dominant: OR = 2.67, 95% CI 1.94-3.67, for FV + VV vs. FF, recessive: OR = 2.38, 95% CI 1.78-3.19, for VV vs. FF + FV, overdominant: OR = 1.58, 95% CI 1.15-2.17, for FV vs. FF+VV, and allele comparison: OR = 1.97, 95% CI 1.70-2.29, for V vs. F, in the overall analyses). Statistically significant associations were also found between rheumatoid arthritis and FCGR3A F158V polymorphisms (recessive: OR = 1.36, 95% CI 1.09-1.69, for VV vs. FF + FV, and allele comparison: OR = 1.15, 95% CI 1.03-1.29, for V vs. F, in the overall analyses). Conversely, the overall analysis identified a negative association between the FCGR2A H131R polymorphism and rheumatoid arthritis in two genetic models (dominant: OR 0.83, 95% CI 0.69-1.00, for HR + RR vs. HH; allelic comparison: OR 0.86, 95% CI 0.76-0.97, for R vs. H).ConclusionThis meta-analysis revealed an association between FCGR3A V158 and an increased risk of immune thrombocytopenia and rheumatoid arthritis. However, this polymorphism is likely to explain only part of the pathogenesis of both diseases. Conversely, a protective association was found between FCGR2A R131 and rheumatoid arthritis. Nevertheless, the quantification of the total genetic contribution of a single gene remains challenging.